Massilia timonae bacteremia: An unusual pathogen of septic abortion - Gawahir A. Ali; Emad B. Ibrahim; Sanjay H. Doiphode; Wael Goravey (IDCases, 2022)
Massilia timonae infections in humans have rarely been reported. To the best of our knowledge, M. timonae has not been previously recognized as a causative agent of obstetric or gynecological infections. Timely identification of this unusual pathogen and the use of targeted antimicrobial therapy are crucial to avoid consequences and treatment failure.